Control de fusiones, ¿Una necesidad? - Rodríguez-Larraín, Alejandro Alfageme (2020)
The sustained growth of the Peruvian economy has generated a series of changes in the business world. Thus, the question arises about the role of the State regarding the rise of acquisitions of already consolidated companies. Is merger control an inefficient mechanism that will only scare away investments or is it necessary in order to be able to protect and implement Competition Law? Throughout the presentRoundtable, three lawyers experts on the matter will debate the correct implementation of said proposals and solutions to the controversy.